2009
DOI: 10.1159/000226425
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cell Wall Thickness between Resistant and Nonresistant Strains of <i>Mycobacterium tuberculosis</i>: Using Transmission Electron Microscopy

Abstract: The ultrastructure of the cell wall of extensively drug-resistant (XDR), multidrug-resistant (MDR) and susceptible tuberculosis (TB) bacilli was viewed under transmission electron microscopy (TEM). Under the TEM, marked differences were observed in the thickness of their cell wall: 20.2 ±1.5 and 17.1 ±1.03 nm for the XDR and MDR TB bacilli, respectively, and 15.6 ± 1.3 nm for the susceptible isolates (p < 0.05). In MDR bacilli, thickening of the cell wall was observed in the intermediate electron-transparent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 38 publications
11
62
0
Order By: Relevance
“…The XDR strain is shorter (p=0.009) and has a ticker cell envelope (p=0.004) than the pan-susceptible strain. These results are in agreement with those published in the literature [5,6].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The XDR strain is shorter (p=0.009) and has a ticker cell envelope (p=0.004) than the pan-susceptible strain. These results are in agreement with those published in the literature [5,6].…”
supporting
confidence: 93%
“…The XDR strain is shorter (p=0.009) and has a ticker cell envelope (p=0.004) than the pan-susceptible strain. These results are in agreement with those published in the literature [5,6].Altogether our data clearly shows the existence of a link between mycobacteria ultrastructure and drug susceptibility. In order to better evaluate these differences a larger number of isolates must be studied.…”
supporting
confidence: 93%
“…Each of anti-TB drugs has a major role in dealing with one of these populations [9]. However, there are still persistent bacterial populations that are not killed by any available TB drugs [10]. Clinically, we have experienced such cases in our TB wards.…”
mentioning
confidence: 99%
“…The development of new technologies and/or the use of known technologies already successfully applied in other fields (such as cancer research) are moving fast into the field of TB. Thus, studies using scanning electron and atomic force microscopy revealed that the M.tb cell wall from MDRand XDR-strains differs from susceptible strains (Velayati et al, 2009a(Velayati et al, , 2009b(Velayati et al, , 2010. Experiments analyzing infected granulomas by using high-resolution magic angle spinning nuclear magnetic resonance (HR-MAS-NMR) showed that we are capable of analyzing the cell wall of M.tb w h e n i n s i d e o f t h e g r a n u l o m a w i t h o u t f u r t h e r manipulation (Somashekar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…What is the cell wall constitution of these strains? Studies performed using transmission electron and atomic force microscopy techniques started to dig into this question showing that MDR-, XDR-, XXDR-and TDR-strains have thicker cell wall and rougher cell surface (supposedly produced by the progressive erosion of their cell wall by the action of the drugs) with tubular extensions than susceptible strains (Velayati et al, 2009a(Velayati et al, , 2010. Because some XDRand TDR-M.tb strains are related to the Beijing family (Velayati et al, 2009b), which are shown to have their cell wall overpopulated with triglycerides, it is plausible to question any relationship between the abundance of a specific hydrophobic lipid on the M.tb cell wall and drug resistance.…”
Section: Lipoglycoconjugates Of the M Tuberculosis Cell Wallmentioning
confidence: 99%